2005
DOI: 10.1295/polymj.37.711
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Thioester Linkages in Bacterial Poly(3-hydroxybutyrate-co-3-mercaptopropionate)s by Poly(3-hydroxybutyrate) Depolymerase Isolated from Ralstonia pickettii T1

Abstract: KEY WORDSPoly(3-hydroxybutyrate-co-3-mercaptopropionate) / Enzymatic Degradation / Thioester / [DOI 10.1295/polymj.37.711] One of major approaches to modify the bacterial poly(3-hydroxybutyrate) (PHB) while reserving its biodegradability has involved the copolymerization of its monomer with some hydroxyalkanoates (HA) via bacterial fermentation, 1 comprising 3-, 4-, 5-and 6-hydroxyalkanoates with various length of the mainchain or various substituents at different positions, such as 3-hydroxypropionate (3HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…This order of weight loss values is similar to the order of enzymatic degradability. [20] From these results, it is clear that the weight loss of the copolymers in the activated sludge supernatant is achieved through microbial action. The results indicate a non-linear relationship between the 3MP unit fraction and weight loss behavior.…”
Section: Entry A)mentioning
confidence: 94%
See 1 more Smart Citation
“…This order of weight loss values is similar to the order of enzymatic degradability. [20] From these results, it is clear that the weight loss of the copolymers in the activated sludge supernatant is achieved through microbial action. The results indicate a non-linear relationship between the 3MP unit fraction and weight loss behavior.…”
Section: Entry A)mentioning
confidence: 94%
“…[19] Zhu et al investigated the enzymatic degradation of poly(3HB-co-3MP) by extracellular PHB depolymerase and reported that the PHB depolymerase hydrolyzed 3HB-3MP linkages but not 3MP-3MP ones. [20] However, no detail on the microbial degradation behavior of poly(3HB-co-3MP) has been reported. To examine a general feature of the microbial degradability of poly(3HB-co-3MP), the degradation behavior of the prepared copolymers was investigated in an activated sludge supernatant at 25 8C at a pH of 7.0.…”
Section: Biodegradability Of Poly(3hb-co-3mp)mentioning
confidence: 99%
“…It can be seen that, similar to P(3HB-co-3HP), the T g value of P(3HB-co-3MP) decreases with increasing 3MP unit content within the comonomer range investigated here, which is in accordance with our previous study. [25] Therefore, from the analysis of the thermal properties it is reasonable to suggest that besides the second comonomer unit content, the sequence distribution is also an important factor that affects the thermal properties, probably by influencing the crystal morphology of the copolymer.…”
Section: Average Sequence Lengthmentioning
confidence: 99%
“…So far, research about the biosynthesis, [14,[19][20][21] thermal properties, [22,23] biodegradation behavior, [24][25][26] etc. of P(3HB-co-3MP) has been intensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation